Typology of the residential structures of medieval Ani - Baeva, Olga (project baikal, 2025)
Drawing on archaeological data and field research, this article proposes a typology for the residential structures of medieval Ani (10th–15th centuries). It investigates diverse dwelling types, from palaces and urban houses to mixed-use buildings and later adapted residences. The examination of their plans, materials and decoration reveals how architecture mirrored the city’s flourishing and eventual decline.
Keywords: Ani; medieval Armenia; residential architecture; building typology; Bagratids; Zakarids; dwellings